Optimization of shell-and-tube heat exchangers using a general design approach motivated by constructal theory - Yang, Jie; Oh, Sun-Ryung; Liu, Wei (International journal of heat and mass transfer, 2014)
A general optimization design method motivated by constructal theory is proposed for heat exchanger design in the present paper. The simplified version of this design approach is suggested and the optimization problem formulations are given. In this method, a global heat exchanger is divided into several sub heat exchangers in series-and-parallel arrangement. The shell-and-tube heat exchanger is utilized for the method application, and the Tubular Exchanger Manufacturers Association (TEMA) standards are rigorously followed for all design parameters, e.g. tube diameter, arrangement, thickness and number. The fitness function is the total cost of the shell-and-tube heat exchangers, including the investment cost for initial manufacture and the operational cost involving the power consumption to overcome the frictional pressure loss. A genetic algorithm is applied to minimize the objective function by adjusting parameters. Three case studies are considered to demonstrate that the new design approach can significantly reduce the total cost compared to the methods of original design, traditional genetic algorithm design, and old constructal design.